Two new species of Bruchomyiinae (Diptera, Psychodidae) from the Neotropical Region - Ježek, Jan; Oboňa, Jozef; Pont, François Le; Maes, Jean-Michel; Mollinedo, Sergio (Zootaxa, 2018)
Males of two Bruchomyiinae species were collected during fieldwork in Central and South America. Boreofairchildia belti Ježek, Oboňa & Le Pont sp. nov. and Notofairchildia motacuensis Ježek, Oboňa & Le Pont sp. nov. are described from a rain forerst site in Nicaragua and a rocky ridge site in Bolivia, respectively. Differential diagnoses are included, and important diagnostic characters illustrated.